Perception of the Costa Rican young adult university population on the measures to avoid the COVID-19 spread during the return to face-to-face lessons in 2022 - Lara Guerrero, Esteban (2023)
A representative sample of the university's young adult population of the Universidad de Costa Rica was surveyed to determine their perception of the sanitary measures implemented to prevent COVID-19 from spreading when they return to face-to-face classes in 2022. The participation of each respondent was voluntary and anonymous, and the data was collected digitally and in person. The results showed that, on average, 85% agreed with the sanitary strategies, which were considered fundamental for public health protection against the virus. Upon returning to face-to-face lessons, 8% of the university students had completed their vaccination scheme. Additionally, 85 and 87% stated that they comply always or almost always with using face masks and hand washing, respectively. According to the findings, the Universidad de Costa Rica population had a favorable perception of the norms established against COVID-19 during the return to face-to-face classes, which were met in a high percentage, demonstrating a significant commitment to public health and general well-being in this population sector.